COLLABORATIVE GOVERNANCE PENANGANAN STUNTING DI KELURAHAN KUREKSARI KABUPATEN SIDOARJO - Rahmadanik, Dida; Murti, Indah; Bella, Vivtania Salsa; Erlanda, Yola (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The concept of Collaborative Governance in efforts to handle stunting in Kureksari Village, Sidoarjo Regency, Collaborative Governance refers to collaboration between government, community, and private sector to achieve common goals. The strategy for stunting involves various parties such as local government, local health centers, non-governmental organizations, and village communities. Collaborative governance also encourages active community participation in the planning and implementation of programs. Through open dialogue and cooperation between parties, the village creates an environment that supports the healthy growth of children. The results of the study show that the collaboration carried out in handling stunting in Kureksari Village has been implemented and has had a good impact, as evidenced by the fact that in 2024, there will be no more cases of stunting; however, the implementers of various programs in handling or preventing stunting continue to provide supervision to pre-stunting children, children Below the Red Line (BGM), malnourished and to all toddlers or children in Kureksari Village so that the problem of stunting can continue to be resolved.